Selective heterofunctionalization of kynurenic acid derivatives - Törteli Levente; Simon Péter; Berkecz Róbert; Szatmári István (2025)
The current study presents selective halogenation of kynurenic acid analogues and further transformation thereof.
Keywords: Kémiai tudományok; Klinikai orvostan